Internalization of the Tolerance Values in Adolescents through the Komunitas Solo Bersimfoni - Luhur Budi Sayekti; Triana Rejekiningsih; Rini Triastuti (Budapest International Research and Critics University, 2022)
This study aims to determine how the efforts to internalize the value of tolerance in adolescents in Surakarta city, Indonesia through the Komunitas Solo Bersimfoni. However, due to the very rapid development of the times and the flow of globalization, the noble values that exist in society are starting to fade and be abandoned by the younger generation, especially teenagers. The value of tolerance is strong, becomes weak and fades in everyday life. Seeing this condition, so the Komunitas Solo Bersimfoni has a goal to re-internalize the values of tolerance to teenagers in the city of Surakarta. This study uses a qualitative approach. The sampling technique used was purposive sampling. Collecting data using interview, observation and documentation methods. The collected data is then analyzed using the Miles and Hubeman model which consists of three steps, namely data reduction, data presentation and drawing conclusions or verification. The results showed that the internalization of the value of tolerance through the Komunitas Solo Bersimfoni was carried out through a cultural approach, namely by inculcating hasthalaku values consisting of mutual cooperation, guyub harmony, grapyak semana, valley manah, ewuh pekewuh, pangerten, andhap asor and tepa selira.. In addition, the Komunitas Solo Bersimfoni also has several programs to internalize the value of tolerance in adolescents, such as the Hasthalaku Compilation FGD program, Adipangastuti School, SB Goes to School, Symphony Class, Hasthalaku Boardgame, Hasthalaku on the street, Symphony Friends, Fragments of Symphony Friends, Solo Bersimfoni Talkshow, Millennial Chat (Ngomel), and Training of Trainers. All programs prepared by the Komunitas Solo Bersimfoni aim to maintain tolerance, to create differences in life in society.